High-thermal-conductivity low-cost magnesium alloy plate and preparation method thereof
By reducing the content of rare earth elements in magnesium alloy and adopting solid solution treatment and pre-deformation composite rolling technology, the problem of low thermal conductivity of rare earth magnesium alloy is solved, and magnesium alloy sheets with excellent mechanical and thermal conductivity are prepared, which are suitable for the heat dissipation needs of highly integrated electronic equipment.
Patent Information
- Application Number
- CN202411823688.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
While improving mechanical properties, existing rare earth magnesium alloys have low thermal conductivity, making it difficult to meet the heat dissipation needs of highly integrated and high-power electronic devices.
A low-risk earth Mg-Gd-Er-Zn-Zr-based magnesium alloy was designed. By reducing the content of rare earth elements, combining solid solution treatment and pre-deformation composite rolling technology, magnesium alloy sheets with excellent mechanical and thermal conductivity were prepared.
It achieves high thermal conductivity (up to 138W/(m·K) and excellent mechanical properties (yield strength 241~295MPa, tensile strength 292~335MPa, elongation 7~14%) of magnesium alloy sheets, and is suitable for heating elements of highly integrated electronic equipment.
Smart Images

Figure HDA0005183699670000011 
Figure HDA0005183699670000012
Abstract
Description
Technical Field
[0001] The invention relates to a magnesium alloy plate having low cost, high thermal conductivity, and both strength and elongation and a preparation method thereof, and specifically belongs to the technical field of metal materials. Background Art
[0002] Magnesium and magnesium alloys have a series of advantages such as light weight, high specific strength and specific stiffness, good electromagnetic shielding, good cutting performance, and no pollution to the environment. They are used in aerospace, automobile manufacturing, national defense construction, and "3C" product manufacturing. With the high integration and high power of internal heating components of 3C electronic products, materials are required to have both excellent heat dissipation and mechanical properties. The thermal conductivity of pure magnesium at room temperature is 156W / (m·K), second only to common commercial metal materials copper (398W / (m·K)) and aluminum (237W / (m·K)). Therefore, it is of great significance to develop magnesium alloy materials that have both mechanical properties and thermal conductivity.
[0003] Research in recent years has shown that rare earth magnesium alloys can not only improve the strength of magnesium alloys, but also improve plasticity, high-temperature creep resistance, etc. For example, Drits et al. increased the room temperature tensile strength of the alloy from 340MPa to 440MPa by adding 6wt.% Y to the Mg-10Gd-0.6Mn (wt.%) alloy. Wen et al. prepared the Mg-14Gd-1Zn-0.6Zr (wt.%) alloy, extruded and aged it, and finally obtained a high-strength magnesium alloy with a tensile strength of 419MPa, a yield strength of 383MPa, and an elongation of 3.8%. However, due to the large difference in atomic radius between rare earth atoms and Mg atoms, the resulting lattice distortion will significantly increase the scattering of phonons and electrons, thereby reducing thermal conductivity. The thermal conductivity of Mg-12Gd high rare earth magnesium alloy after solution treatment is only 56.9W / (m·K), and the thermal conductivity of the more mature WE54 and WE43 magnesium alloys after solution treatment is only 52.0W / (m·K) and 51.3W / (m·K). In addition, the current deformation thermal conductive magnesium alloys are only concentrated in the non-rare earth Mg-Zn system and Mg-Al system, and the research on rare earth deformation thermal conductive magnesium alloys is still relatively limited. Therefore, it is of great practical significance to develop a rare earth magnesium alloy with simple process and excellent performance and integrated mechanical-thermal conductivity.
[0004] In view of the above problem of imbalance between mechanical properties and thermal conductivity, the present invention proposes the following preparation process: a low-rare earth Mg-Gd-Er-Zn-Zr magnesium alloy is designed and developed, wherein the mass percentage of rare earth element Gd is ≤6%, the mass percentage of Er is ≤1%, the mass percentage of Zn is ≤6%, the mass percentage of Zr is ≤0.6%, and the total rare earth content is ≤7%. After melt casting, solid solution is carried out, and pre-deformation composite rolling is performed to prepare a magnesium alloy sheet with a smooth surface, good formability, and both mechanical and thermal conductivity properties. Summary of the invention
[0005] Aiming at the shortcomings of the existing deformed magnesium alloys with high rare earth content and low thermal conductivity, the present invention proposes a magnesium alloy sheet preparation technology that reduces alloy cost, improves thermal conductivity and takes into account mechanical properties. The present invention is characterized in that the rare earth element content in the alloy is reduced and controlled to ≤7%; after the cast alloy is subjected to solid solution treatment, the pre-deformation composite rolling process is adopted to roll the slab at different temperatures to obtain excellent thermal conductivity and mechanical properties. This invention breaks through the conflict between the thermal conductivity and mechanical properties of the current deformed magnesium alloy, and obtains a magnesium alloy with an average grain size of 4.3μm to 12.9μm and containing broken Mg3Zn3(Gd,Er)2 phases. The yield strength of the rolled sheet is 241 to 295MPa, the tensile strength is 292 to 335MPa, the elongation is 7 to 14%, and the thermal conductivity can reach 54 to 138W / (m·K). It is a new type of magnesium alloy sheet that meets the thermal conductivity requirements of electronic materials.
[0006] The technical solution of this patent is: a low-cost high thermal conductivity magnesium alloy plate, the selected magnesium alloy is Mg-Gd-Er-Zn-Zr system, Gd 2-6wt.%, Er≤1wt.%, Zn 4-6wt.%, Zr≤0.6wt.%, magnesium content is the balance; the preparation process of the above plate includes the following steps:
[0007] (1) Raw material preparation: weigh the master alloy, commercial pure magnesium (99.99 wt.%), and pure zinc block according to the above alloy mass ratio, the master alloy Mg-Gd master alloy is preferably Mg-30 wt.% Gd, the Mg-Er master alloy is Mg-20 wt.% Er, and the Mg-Zr master alloy is Mg-24 wt.% Zr, and remove the oxide scale on the surface of the raw materials;
[0008] (2) Smelting pure magnesium: The pure magnesium ingot in step (1) is placed in a clean graphite crucible, and then placed in a resistance furnace at 200 to 300° C. for preheating for about 10 to 20 minutes to remove moisture in the crucible;
[0009] (3) Melting the master alloy: the pure magnesium ingot preheated in step (2) and the graphite crucible are heated to 720-730° C., and when the magnesium is completely melted, two gases are used for protection during the melting process, nitrogen (N2) is the carrier gas, and sulfur hexafluoride (SF6) is the protective gas, and the volume ratio of nitrogen to sulfur hexafluoride is 6:1; then the prepared Mg-Gd master alloy is placed in the molten magnesium melt, the temperature is adjusted to 730-750° C., and the pure Zn and Mg-Er master alloy blocks are added, and then the temperature is adjusted to 730-760° C., and the Mg-Zr master alloy block is added after the temperature is adjusted to 730-760° C. and the Mg-Zr master alloy block is added after the temperature is adjusted to 730-760° C. and the SF6 is kept at the temperature for 10-15 minutes. The scum floating on the surface of the solution is removed and stirred for 3-5 minutes;
[0010] (4) Casting: Adjust the temperature to 720-730°C and let it stand for 15 minutes, remove the crucible and remove the slag, and when the melt temperature reaches 720-725°C, cast it into a metal mold, and obtain an ingot after the Mg alloy liquid cools naturally;
[0011] (5) Solution treatment: The magnesium alloy is placed in a box-type muffle furnace, and after the holding temperature is set to 510°C and the holding temperature is kept for 12 hours, it is placed in water for quenching; the magnesium alloy after the solution treatment is then cut into slabs of appropriate size, and the magnesium alloy slabs are placed in a heating furnace and the holding temperature and holding time are set, and then placed on a rolling mill for pre-deformation composite rolling. The pre-deformation reduction in the first stage is 40%, and the total reduction after the second stage rolling is 80%, thereby obtaining a high thermal conductivity magnesium alloy with refined grains and a crushed Mg3Zn3(Gd,Er)2 strengthening phase.
[0012] The molten magnesium alloy ingot is solution treated and then cut into magnesium alloy slabs of appropriate size. The first stage of pre-deformation is carried out at 400°C to 450°C. After two pre-deformations, the reduction is 40%. The rolling speed is 10m / min. The furnace is returned to the furnace for insulation for 10 to 15 minutes between each pass, and the reduction of a single pass is 20% to 25%. The pre-deformed plate is subjected to composite rolling, rolled at 350°C to 400°C, and the total deformation is 80% in two passes. The rolling speed is 10m / min. The furnace is returned to the furnace for insulation for 10 to 15 minutes between each pass, and the reduction of a single pass is 20% to 25%.
[0013] The thickness of the pre-deformed plate obtained by the present invention is 6.0 mm to 6.5 mm, the surface is smooth and without cracks. The thickness of the plate finally obtained is 2.0 mm to 2.3 mm, the surface is smooth and without cracks.
[0014] The grain size of the plate finally obtained is 4.3μm to 12.9μm. A broken Mg3Zn3(Gd,Er)2 phase distributed in a lath shape is produced, and the broken particle size of the second phase is about 1.5μm to 8μm.
[0015] The yield strength of the rolled plate is 241-295 MPa, the tensile strength is 292-335 MPa, the elongation is 7-14%, and the thermal conductivity can reach 54-138 W / (m·K).
[0016] The alloy has excellent mechanical and thermal conductivity properties and can be used in structural components in aerospace, automobile, 3C electronic equipment and other fields.
[0017] The alloy mechanical property test of the present invention is carried out according to the relevant provisions of the national standard GB / T228-2010 "Room Temperature Tensile Test Method for Metallic Materials"; the thermal conductivity is tested according to the flash method ASTME1461-2013 international standard.
[0018] The present invention has the following advantages:
[0019] 1. The present invention reduces the rare earth content in the alloy and saves raw material costs.
[0020] 2. The present invention adopts a pre-deformation composite rolling process, which greatly improves the formability of the alloy and reduces the number of rolling passes. It adopts a convenient, effective and feasible preparation technology to improve production efficiency and reduce production costs.
[0021] 3. The alloy plate prepared by the process of the present invention obtains a broken strengthening phase and a microstructure with a fine grain size.
[0022] 4. The alloy plate prepared by the process of the present invention has a thermal conductivity of up to 138W / (m·K), while taking into account the maximum yield strength of 295MPa and the mechanical properties of tensile strength of 310MPa, and can be used for highly integrated heating elements in modern electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 OM image of the alloy microstructure with a reduction of 80% prepared in Example 5 of the present invention;
[0024] Figure 2 This is a SEM image of the microstructure of the alloy prepared in Example 5 of the present invention with a reduction of 80%; Specific implementation methods
[0026] The present invention is further described below in conjunction with embodiments. The following embodiments are all implemented based on the technical solution of the present invention, but the protection scope of the invention is not limited to the following embodiments.
[0027] Melting pure magnesium: put the pure magnesium ingot into a clean graphite crucible, and then put them into the furnace of a resistance furnace at 200-300℃ for preheating for about 10-20 minutes to remove moisture in the crucible;
[0028] Melting the master alloy: heat the preheated pure magnesium ingot and the graphite crucible together to 720-730°C, wait until the magnesium is completely melted, and use two gases for joint protection during the smelting process, nitrogen (N2) as the carrier gas, sulfur hexafluoride (SF6) as the protective gas, and the volume ratio of nitrogen to sulfur hexafluoride is 6:1; then put the prepared Mg-Gd master alloy into the molten magnesium melt, adjust the temperature to 730-750°C, keep it warm and stand for 10-15 minutes, then add the pure Zn and Mg-Er master alloy blocks, then adjust the temperature to 730-760°C, keep it warm and stand for 10-15 minutes, then add the Mg-Zr master alloy block, adjust the temperature to 730-760°C and keep it warm and stand for 10-15 minutes, then remove the scum floating on the surface of the solution and stir it for 3-5 minutes;
[0029] Casting: Adjust the temperature to 720-730℃ and let it stand for 15min, take out the crucible and remove the slag, and when the melt temperature reaches 720-725℃, cast it into a metal mold, and the Mg alloy liquid will be naturally cooled to obtain an ingot;
[0030] Solution treatment: put the magnesium alloy into a box-type muffle furnace, set the insulation temperature to 510°C, keep it for 12 hours, and then quench it in water.
[0031] Example 1
[0032] The Mg-2Gd-1Er-6Zn-0.5Zr alloy obtained by ordinary melting and casting was subjected to solution treatment, followed by cutting and milling to obtain a rolled blank, which was then placed in a holding furnace for 20 minutes at a temperature of 425°C. The rolling rate was set to 10m / min, and the deformation amount per pass was 20%. After two passes of rolling, the holding time between each pass was 15min, and the pre-deformation reduction was 40%, a plate with a thickness of 6.36mm was obtained. The pre-deformed plate was then kept in a holding furnace at 400°C and rolled in two passes, with a holding time of 10min between passes and a single pass reduction of 20%. Finally, a rolled alloy with a total reduction of 80% was obtained, with a plate thickness of 2.12mm and a grain size of 8.6μm. Finally, the tensile strength, yield strength and elongation were 335.4MPa, 278.2MPa and 9.3% respectively, and the thermal conductivity reached 126.8W / (m·k).
[0033] Example 2
[0034] The steps are the same as those in Example 1, except that the pre-deformation rolling temperature is 400°C and the second-stage composite rolling temperature is 375°C. Finally, an alloy with a plate thickness of 2.04 mm and a grain size of 5.2 μm is obtained. The tensile strength, yield strength and elongation are 328.4 MPa, 272.1 MPa and 14.9% respectively, and the thermal conductivity reaches 124.8 W / (m·k).
[0035] Example 3
[0036] The Mg-4Gd-1Er-6Zn-0.5Zr alloy obtained by ordinary melting and casting was subjected to solid solution treatment, followed by cutting and milling to obtain a rolled blank, which was then placed in a holding furnace for 20 minutes at a temperature of 400°C. The rolling rate was set to 10m / min, the deformation amount per pass was 20%, and after two rolling passes, the holding time between each pass was 15min, and the pre-deformation reduction was 40%, a plate with a thickness of 6.48mm was obtained. The pre-deformed plate is then kept warm in a holding furnace at 400°C and rolled in two passes with a holding time of 10 minutes between passes and a single pass reduction of 20%. Finally, a rolled alloy with a total reduction of 80% is obtained. The plate thickness is 2.16 mm and the grain size is 7.1 μm. The tensile strength, yield strength and elongation are 292 MPa, 241 MPa and 14.1%, respectively, and the thermal conductivity is 129.0 W / (m·k).
[0037] Example 4
[0038] The steps are the same as those in Example 3, except that the pre-deformation rolling temperature is 400°C and the second-stage composite rolling temperature is 375°C. Finally, an alloy with a plate thickness of 2.04 mm and a grain size of 5.3 μm is obtained. The tensile strength, yield strength and elongation are 302 MPa, 279 MPa and 11.4% respectively, and the thermal conductivity is 130.3 W / (m·k).
[0039] Example 5
[0040] The Mg-6Gd-1Er-6Zn-0.5Zr alloy obtained by ordinary melting and casting was subjected to solution treatment, followed by cutting and milling to obtain a rolled blank, which was then placed in a holding furnace for 20 minutes at a temperature of 400°C. The rolling rate was set to 10m / min, and the deformation amount per pass was 20%. After two passes of rolling, the holding time between each pass was 15min, and the pre-deformation reduction was 40%, a plate with a thickness of 6.24mm was obtained. The pre-deformed plate was then kept in a holding furnace at 400°C and rolled in two passes, with a holding time of 10min between passes and a single pass reduction of 20%. Finally, a rolled alloy with a total reduction of 80% was obtained, with a plate thickness of 2.08mm and a grain size of 5.2μm. Its tensile strength, yield strength and elongation are 310MPa, 295MPa and 12% respectively, and its thermal conductivity reaches 138W / (m·k).
[0041] Example 6
[0042] The steps are the same as those in Example 5, except that the pre-deformation rolling temperature is 450°C and the second-stage composite rolling temperature is 350°C. Finally, an alloy with a plate thickness of 2.04 mm and a grain size of 4.3 μm is obtained. The tensile strength, yield strength and elongation are 309 MPa, 286 MPa and 7.8% respectively, and the thermal conductivity reaches 135 W / (m·k).
[0043] Example 7
[0044] The Mg-6Gd-1Er-2Zn-0.6Zr alloy obtained by ordinary melting and casting was subjected to solid solution treatment, followed by cutting and milling to obtain a rolled blank, which was then placed in a holding furnace for 20 minutes at a temperature of 450°C. The rolling rate was set to 10m / min, the deformation amount per pass was 20%, and after two rolling passes, the holding time between each pass was 15min, and the pre-deformation reduction was 40%, a plate with a thickness of 6.06mm was obtained. The pre-deformed plate is then kept warm in a holding furnace at 400°C and rolled in two passes with a holding time of 10 minutes between passes and a single pass reduction of 20%. Finally, a rolled alloy with a total reduction of 80% is obtained. The plate thickness is 2.02 mm and the grain size is 5.9 μm. The tensile strength, yield strength and elongation are 293 MPa, 247.2 MPa and 9.36% respectively, and the thermal conductivity is 54.2 W / (m·k).
Claims
1. A method for preparing a low-cost high thermal conductivity magnesium alloy sheet, wherein the selected magnesium alloy is Mg-Gd-Er-Zn-Zr system, Gd 2-6wt.%, Er≤1wt.%, Zn 4-6wt.%, Zr≤0.6wt.%, and the magnesium content is the balance; the preparation process of the above-mentioned sheet comprises the following steps: (1) Raw material preparation: weigh the master alloy, commercial pure magnesium (99.99 wt.%), and pure zinc block according to the above alloy mass ratio, wherein the master alloy is Mg-Gd master alloy, Mg-Er master alloy, and Mg-Zr master alloy, and remove the oxide scale on the surface of the raw materials; (2) Smelting pure magnesium: The pure magnesium ingot in step (1) is placed in a clean graphite crucible, and then placed in a resistance furnace at 200 to 300° C. for preheating for about 10 to 20 minutes to remove moisture in the crucible; (3) Melting the master alloy: the pure magnesium ingot preheated in step (2) and the graphite crucible are heated to 720-730° C., and when the magnesium is completely melted, two gases are used for protection during the melting process, nitrogen (N2) is the carrier gas, and sulfur hexafluoride (SF6) is the protective gas, and the volume ratio of nitrogen to sulfur hexafluoride is 6:1; then the prepared Mg-Gd master alloy is placed in the molten magnesium melt, the temperature is adjusted to 730-750° C., and the pure Zn and Mg-Er master alloy blocks are added, and then the temperature is adjusted to 730-760° C., and the Mg-Zr master alloy block is added after the temperature is adjusted to 730-760° C. and the Mg-Zr master alloy block is added after the temperature is adjusted to 730-760° C. and the SF6 is kept at the temperature for 10-15 minutes. The scum floating on the surface of the solution is removed and stirred for 3-5 minutes; (4) Casting: Adjust the temperature to 720-730°C and let it stand for 15 minutes, remove the crucible and remove the slag, and when the melt temperature reaches 720-725°C, cast it into a metal mold, and obtain an ingot after the Mg alloy liquid cools naturally; (5) Solution treatment: The magnesium alloy is placed in a box-type muffle furnace, and after the holding temperature is set to 510°C and the holding temperature is kept for 12 hours, it is placed in water for quenching; the magnesium alloy after the solution treatment is then cut into slabs of appropriate size, and the magnesium alloy slabs are placed in a heating furnace and the holding temperature and holding time are set, and then placed on a rolling mill for pre-deformation composite rolling. The pre-deformation reduction in the first stage is 40%, and the total reduction after the second stage rolling is 80%, thereby obtaining a high thermal conductivity magnesium alloy with refined grains and a crushed Mg3Zn3(Gd,Er)2 strengthening phase.
2. The method according to claim 1, characterized in that The master alloy is preferably Mg-30wt%Gd, the Mg-Er master alloy is Mg-20wt.%Er, and the Mg-Zr master alloy is Mg-24wt%Zr.
3. The method according to claim 1, characterized in that The molten magnesium alloy ingot is solution treated and then cut into magnesium alloy slabs of appropriate size. The first stage of pre-deformation is carried out at 400°C to 450°C. After two pre-deformations, the reduction is 40%. The rolling speed is 10m / min. The furnace is returned to the furnace for insulation for 10 to 15 minutes between each pass, and the reduction of a single pass is 20% to 25%. The pre-deformed plate is subjected to composite rolling, rolled at 350°C to 400°C, and the total deformation is 80% in two passes. The rolling speed is 10m / min. The furnace is returned to the furnace for insulation for 10 to 15 minutes between each pass, and the reduction of a single pass is 20% to 25%.
4. The method according to claim 1, characterized in that The thickness of the pre-deformed plate is 6.0 mm to 6.5 mm, the surface is smooth and there is no crack; the thickness of the finally obtained plate is 2.0 mm to 2.3 mm, the surface is smooth and there is no crack.
5. The method according to claim 1, characterized in that The grain size of the plate finally obtained is 4.3μm to 12.9μm. A broken Mg3Zn3(Gd,Er)2 phase distributed in a lath shape is produced, and the broken particle size of the second phase is about 1.5μm to 8μm.
6. The method according to claim 1, characterized in that The yield strength of the rolled plate is 241-295 MPa, the tensile strength is 292-335 MPa, the elongation is 7-14%, and the thermal conductivity can reach 54-138 W / (m·K).
7. A high thermal conductivity magnesium alloy sheet prepared according to the method according to any one of claims 1 to 6.
8. Application of the high thermal conductivity magnesium alloy sheet prepared by the method according to any one of claims 1 to 4 in structural components in the fields of aerospace, automobiles, 3C electronic equipment, etc.